2023
DOI: 10.21203/rs.3.rs-3170858/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions to increase vaccination in vulnerable groups: rapid overview of reviews

Abstract: Objective Groups which are marginalised, disadvantaged or otherwise vulnerable have lower uptake of vaccinations. This differential has been amplified in COVID-19 vaccination compared to (e.g.) influenza vaccination. This overview assessed the effectiveness of interventions to increase vaccination in underserved, minority or vulnerable groups. Methods In November 2022 we searched four databases for systematic reviews including RCTs of interventions to increase vaccination in underserved, minority or vulnerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The protocol for this overview of reviews was registered on Prospero: CRD42021293355 [5]. We adapted appropriate rapid systematic review methods for this rapid overview and reported it following PRIOR reporting guidelines where possible [6].…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for this overview of reviews was registered on Prospero: CRD42021293355 [5]. We adapted appropriate rapid systematic review methods for this rapid overview and reported it following PRIOR reporting guidelines where possible [6].…”
Section: Methodsmentioning
confidence: 99%